EFEKTIVITAS PELAKSANAAN ZAKAT SECARA ONLINE (STUDI BADAN AMIL ZAKAT NASIONAL KOTA PADANG) - Fauzi Yati; Putri Rahmani (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This article looks at the effectiveness of online zakat implementation at the Padang City National Amil Zakat Agency (Baznas Padang City). This research was conducted because almost all sectors of life have been transformed into digitalization. Apart from the rapid technological advances, Covid-19 has also been forced to change. Padang City Baznas took part in this change by implementing a digitalization system in zakat receipts, as well as contracts made with muzakki that were not carried out directly. This article is a qualitative research. Data were collected through observation, interviews, and document collection. The results of the study indicate that the digital services of the Padang City Baznas are divided into three forms, first, through Transfers via the Padang City Baznas Account; second, the Padang City Baznas Website; and third, Scan the QR Code. For the sake of the perfection of the system, the City of Padang Baznas utilizes social media to campaign for the community with various available platforms. Even though it was carried out in various ways, it was found that the implementation of online zakat in the Padang City Baznas had not been running effectively. This is proven based on the recapitulation of incoming zakat. The Padang City Baznas has not separated the zakat paid by muzakki online or offline. While this is important in the world of digitization as a form of transparency. Then, the ineffectiveness is caused by the uneven distribution of the internet network.